2020
DOI: 10.24018/ejbmr.2020.5.2.207
|View full text |Cite
|
Sign up to set email alerts
|

The Supervisor’s Support For Silence And The Organizational Commitment: The Mediating Role Of Organizational Silence Behavior

Abstract: The aim of this study was to test the relationship between supervisor support for silence and organizational commitment, as well as testing the relationship between supervisor support for silence and organizational silence behavior.  The study also aimed to identify the relationship between organizational silence behavior and organizational commitment, as well as the test of the mediation role of silence behavior in the relationship between supervisor support for silence and organizational commitment. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 20 publications
(49 reference statements)
2
2
0
Order By: Relevance
“…The level of the ‘support of supervisor for silence’ subscale is also moderate. This result is consistent with Rayan et al (2020), who explained that if the supervisors' actions are supportive of silence, and this will hugely reshape the employees' behaviour. This is because the supervisors are the representatives of the organisation, and they interact with employees daily.…”
Section: Discussionsupporting
confidence: 92%
“…The level of the ‘support of supervisor for silence’ subscale is also moderate. This result is consistent with Rayan et al (2020), who explained that if the supervisors' actions are supportive of silence, and this will hugely reshape the employees' behaviour. This is because the supervisors are the representatives of the organisation, and they interact with employees daily.…”
Section: Discussionsupporting
confidence: 92%
“…So, H1 cannot be rejected. The results of Cetin (2020), Aflatoon et al (2018), andRayan et al (2020), who also observed a negative connection between OS and OC, agree with this conclusion. Therefore, employees' commitment levels decline when they keep silent at work, which eventually has an impact on organizational performance.…”
Section: 2: Correlation Matrixsupporting
confidence: 55%
“…OT adversely impacted OS, and OS adversely impacted JS and OC, based on an investigation using partial least squares structural equation modeling (PLS-SEM). In an investigation by Rayan, Ali, and Abdel Moneim (2020) exploring the affinity between OS behavior and OC, 365 employees of Egypt's Assiut University took part. The findings revealed a negative relationship between OC and OS behavior.…”
Section: Empirical Reviewmentioning
confidence: 99%
“…Therefore, understanding and interpreting silence is more difficult than speaking. In recent research on the topic of silence, it has been observed that concepts such as organizational learning (Köse & Güçlü, 2017), organizational culture (Parcham & Ghasemizad, 2017;Sholekar & Shoghi, 2017;Yalçınsoy, 2019), organizational commitment (Bayramoğlu & Çetinkanat, 2020;Çetin, 2020;Rayan, Ali & Moneim, 2020;Sadeghi & Ravazi, 2020;Vardarlıer & Akıner, 2020), organizational trust (Helmiati, Abdillah, Anita & Nofianti, 2018), school climate (Algarni, 2020) and the mediating effect of perceived stress and trust (Dong & Chung, 2020) were mostly discussed.…”
Section: Introductionmentioning
confidence: 99%